Conflicts of land expropriation in China during 2006–2016: An overview and its spatio-temporal characteristics. (July 2018) - Lin, Qiaowen; Tan, Shukui; Zhang, Lu; Wang, Siliang; Wei, Chao; Li, Yanan
Abstract: In recent years conflicts of land expropriation in China have received a lot of concern. Recent systematic reviews highlight causes, types and resolution of land conflicts, yet very few of these studies have considered the spatial-temporal characteristics of the issue. Utilizing spatial statistical analysis and statistical software, this paper aims to build a contextual overview on Chinese land expropriation conflicts and explore spatial and temporal distribution of it during 2006–2016. Correlations of land conflict intensity with per capita GDP and urbanization rate have been studied. This paper indicates that farmers should share responsibilities for the occurrence of land conflicts as well due to their improper behavior. Offensive language and acts of defiance make the issue more complicated. Furthermore, the study reveals that the number of land expropriation conflicts in China has declined since 2013 due to government's positive actions. Overall, the conflict of land expropriation in space is categorized as "high intensity in the south and low intensity in the north". The most conflicted areas in China are south and the southwest. Among them, Guangdong and Yunnan are particular regions with a high intensity of land conflicts. Last but not least, by use of data we have shown that land conflict intensity in China does not have a statistically significant spatial pattern on the whole. However, the relationship between per capita GDP and land conflict intensity has a statistically dispersed spatial pattern.